Effect of pH on Mycelial Growth and Sporulation of Postharvest Pathogen Colletotrichum gloeosporioides (Penz.) Penz & Sacc. and Pestalotiopsis mangiferae ( Henn.) Steyaert - Majumdar, Niren; Mandal, Nakul Chandra (International Journal of Bio-resource and Stress Management, 2018)
Among the plethora of postharvest pathogens causing enormous losses Colletotrichum gloeosporioides is an important polyphagous pathogen, Pestalotiopsis mangiferae is monophagus to mango. A study was conducted with these two pathogens obtained from banana and mango to find out the optimum pH level for growth and sporulation as well as the possible utilization of this knowledge in developing management strategy of quiescent infections by them. Both fungi grew at Potato Dextrose Broth and PDA within the pH regime 4.0–9.0 tested at 28±1 oC, although growth rate differs significantly at different hours of incubation. The optimum pH for growth and sporulation differs significantly. The optimum pH for both growth and sporulation was 5.0 in PDA. In case of potato dextrose broth pH 6.0 was optimum for C. gloeosporioides and P. mangiferae has wide adaptability within ph range 4.0–6.0. Both pathogens sporulate in all the pH regime 4.0–9.0, however C. gloeosporioides best sporulate at pH 5.0 and P. mangiferae at pH.8.0 The role of pH modulated host resistance has been discussed.